2012
DOI: 10.1111/j.1939-1676.2012.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐Modulated and Image‐Guided Radiation Therapy for Treatment of Genitourinary Carcinomas in Dogs

Abstract: Background: External beam radiation therapy can be used to treat pelvic tumors in dogs, but its utility is limited by lack of efficacy data and associated late complications.Hypothesis/Objectives: The objective of this study was to assess local tumor control, overall survival, and toxicosis after intensity-modulated and image-guided radiation therapy (IM/IGRT) for treatment of genitourinary carcinomas (CGUC) in dogs.Animals: 21 client-owned dogs. Methods: A retrospective study was performed. Medical records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 33 publications
2
91
0
1
Order By: Relevance
“…When radiation was combined with mitoxantrone and piroxicam in one study, the reported response rate of 22% was not significantly different compared to the use of mitoxantrone and piroxicam alone [25]. More recently, the use of image guided intensity modulated radiation (IG/IMRT) with or without adjunctive chemotherapy in one study reported a median survival time of 614 days [26]. In addition, adjuvant low-dose palliative radiation therapy resulted in a 61% objective response rate, with 100% of dogs experiencing clinical benefit (CR, PR, SD) within 6 weeks of radiation therapy [27].…”
Section: Introductionmentioning
confidence: 99%
“…When radiation was combined with mitoxantrone and piroxicam in one study, the reported response rate of 22% was not significantly different compared to the use of mitoxantrone and piroxicam alone [25]. More recently, the use of image guided intensity modulated radiation (IG/IMRT) with or without adjunctive chemotherapy in one study reported a median survival time of 614 days [26]. In addition, adjuvant low-dose palliative radiation therapy resulted in a 61% objective response rate, with 100% of dogs experiencing clinical benefit (CR, PR, SD) within 6 weeks of radiation therapy [27].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited literature regarding efficacious treatment of canine PC. As most dogs are euthanized due to local obstructive disease, research has focused on local treatment such as complete or partial prostatectomy, photodynamic therapy and radiation therapy (RT), either in the form of intraoperative,intensity‐modulated or image‐guided RT …”
Section: Introductionmentioning
confidence: 99%
“…Dogs with larger tumors invading locoregionally or with evidence of metastasis (ie, more advanced stage) have a less favorable prognosis with shorter survival times or shorter time to obstruction. 2,7,47 Dogs at an increased risk for metastasis include younger dogs (increased risk of lymph node metastasis), dogs with prostate involvement (increased risk of distant metastasis), and dogs with larger tumors (increased risk for both nodal and distant metastasis). 2,47 Many publications describe heavily pretreated dogs or dogs that go on to receive other treatments, which makes survival data for dogs with this tumor challenging to summarize.…”
Section: Evaluation Of Outcome and Long-term Recommendationsmentioning
confidence: 99%
“…However, this modality is not suitable for dogs with distant metastatic disease, and owners should be counseled about risks of side effects, as discussed. 47 Palliative radiation therapy may be used to relieve severe clinical signs, urethral obstruction, or pain from bone metastases. The risk of late side effects to the gastrointestinal and urinary tract is theoretically considerable with palliative protocols, but clinically not of great concern because of the palliative intent-most patients do not live long enough to experience late side effects.…”
Section: Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation